2016
DOI: 10.3758/s13428-016-0807-0
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling narrow and coarse semantic networks in the brain: The role of computational models of word meaning

Abstract: There has been a recent boom in research relating semantic space computational models to fMRI data, in an effort to better understand how the brain represents semantic information. In the first study reported here, we expanded on a previous study to examine how different semantic space models and modeling parameters affect the abilities of these computational models to predict brain activation in a datadriven set of 500 selected voxels. The findings suggest that these computational models may contain distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…For the USF norms and the MTurk data, the number indicates the word association strength, calculated as the proportion of participants who produced the target word in response to a cueparticipants were asked to write down a word that came to mind (e.g., Bline^) when presented with a prompt word (e.g., Bborder^) ** USF = the word associations based on the University of South Florida free word association norms of (Nelson et al, 1998). The USF norms include only single words and did not include Bhealth care* ** MTurk = the word associations based on 600 Mechanical Turk responders of (Schloss et al, 2016). The MTurk data include only single words and did not include Bhealth care1 Study Two: Voters' self-reported political engagement and their voting behavior Study One was primarily concerned with how the presidential candidates and their parties represented political concepts and the changing representations over time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the USF norms and the MTurk data, the number indicates the word association strength, calculated as the proportion of participants who produced the target word in response to a cueparticipants were asked to write down a word that came to mind (e.g., Bline^) when presented with a prompt word (e.g., Bborder^) ** USF = the word associations based on the University of South Florida free word association norms of (Nelson et al, 1998). The USF norms include only single words and did not include Bhealth care* ** MTurk = the word associations based on 600 Mechanical Turk responders of (Schloss et al, 2016). The MTurk data include only single words and did not include Bhealth care1 Study Two: Voters' self-reported political engagement and their voting behavior Study One was primarily concerned with how the presidential candidates and their parties represented political concepts and the changing representations over time.…”
Section: Resultsmentioning
confidence: 99%
“…In our modeling, we trained the model using both algorithms as implemented in Python's Gensim package (Rehurek, 2010) and concatenated the representations into vectors with 4,000 dimensions. The decision to use concatenated vector representations was based on the consideration that (a) the two algorithms may be sensitive to different types of word associations (e.g., dominant, paradigmatic, vs. non-dominant associations), which may implicate different processing mechanisms (Jung-Beeman, 2005), and (b) previous work has suggested that concatenated vectors can in some cases provide increased accuracy in representing subtle semantic differences (Fyshe et al, 2013;Schloss & Li, 2016). 1 We used word2vec's default settings, with a window size of five and a minimum word-count of five (words that were used less than five times were excluded) for all models reported below except for the time-course analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Representational similarity as measured by voxel analysis is also becoming increasingly important in neuro-imaging approaches that try to uncover the structure of semantic memory. Across a range of studies, the fMRI evidence indicates that the pattern of activation across different areas of the brain when reading common words (Mitchell et al, 2008) can be predicted from distributional lexico-semantic models (Schloss & Li, 2016). Against this backdrop, it seems sensible to consider how the SWOW-EN norms might be used to measure semantic similarity.…”
Section: Using Word Associations To Estimate Semantic Similaritymentioning
confidence: 99%
“…By contrast, semantic vector representations of concepts (e.g. Latent Semantic Analysis, (Dumais, 2004)) have limited linguistic interpretability, although the use of such representations has been shown to be predictive of neural activation (e.g., Mitchell et al, 2008;Murphy et al, 2012;Schloss & Li, 2016).…”
Section: Configurations Of Concept Representations In Sentences Acrosmentioning
confidence: 99%